Redhead by the side of the road - Tyler, Anne (New York : Alfred A. Knopf, 2020)
"From the beloved and best-selling Anne Tyler, a sparkling new novel about misperception, second chances, and the sometimes elusive power of human connection. Micah Mortimer is a creature of habit. A self-employed tech expert, superintendent of his Baltimore apartment building, cautious to a fault behind the steering wheel, he seems content leading a steady, circumscribed life. But one day his routines are blown apart when his woman friend (he refuses to call anyone in her late thirties a "girlfriend") tells him she's facing eviction, and a teenager shows up at Micah's door claiming to be his son. These surprises, and the ways they throw Micah's meticulously organized life off-kilter, risk changing him forever. An intimate look into the heart and mind of a man who finds those around him just out of reach, and a funny, joyful, deeply compassionate story about seeing the world through new eyes, Redhead by the Side of the Road is a triumph, filled with Anne Tyler's signature wit and gimlet-eyed observation"--